Cost-Effectiveness Analysis of a Latent Tuberculosis Screening Program Among Healthcare Personnel - Niludi Ranwanee Yasaratna MD; Manuj Chrishantha Weerasinghe MD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Screening high-risk groups for Latent Tuberculosis Infection (LTBI) is crucial for TB elimination, as the large global reservoir of Mycobacterium tuberculosis bacilli poses a significant challenge to TB control globally. Assessing the cost-effectiveness of LTBI screening strategies is also crucial in determining the optimal approach. In 2022, Sri Lanka initiated a new program to manage latent tuberculosis infection among high-risk groups, including healthcare personnel, which recorded an 18% Latent Tuberculosis prevalence. This study aimed to evaluate the cost-effectiveness of implementing a screening program for Healthcare Personnel as part of this initiative in Sri Lanka. A decision tree model was developed to assess the cost-effectiveness of LTBI screening among Healthcare Personnel from the health system perspective, using secondary data from 2021 to 2022. The decision tree model was used to evaluate the cost-effectiveness of initiating LTBI screening for Healthcare Personnel in government hospitals. The findings are presented as the Incremental Cost-Effectiveness Ratio (ICER), compared to locally appropriate cost-effectiveness thresholds. The direct costs incurred for the standard LTBI tests and prophylaxis were assessed at the program level. The ICER represents the incremental cost of LTBI screening per Disability Adjusted Life Year (DALY) gained by preventing future active TB cases through treatment of latent TB infection. The total cost for managing an active TB case was $80.44, markedly higher than the $20.84 cost for a Latent TB case. The total cost difference between managing an active TB case and a Latent TB case was $59.60. The Incremental Cost-Effectiveness Ratio was $2381.29 per Disability Adjusted Life Year averted. The decision analysis model indicated that screening Healthcare Personnel for latent tuberculosis infection is highly cost-effective and can be recommended for implementation in Sri Lanka.